2013
DOI: 10.1002/stem.1387
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Ligament Stem Cells Regulate B Lymphocyte Function via Programmed Cell Death Protein 1

Abstract: Periodontal ligament stem cells (PDLSCs) have provided novel cell sources for tooth and periodontal tissue regeneration. Allogeneic PDLSCs can reconstruct periodontal ligament tissue that has been damaged by periodontal diseases and regulate T-cell immunity. However, the effect of PDLSCs on B cells remains unknown. Here, we treated periodontitis in a miniature pig model using allogeneic PDLSCs and showed a reduction in humoral immunity in the animals. When cocultured with normal B cells, human PDLSCs (hPDLSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 49 publications
3
90
0
1
Order By: Relevance
“…It has been demonstrated that allogeneic PDLSC transplantation into swine periodontal defect models did not induce immunorejection by showing no enhancement of T-cell and B-cell proliferation and immunoglobulin production and suggested the possibility of periodontal regeneration using allogeneic PDLSCs. 8,31 In this study, we used PDLSCs derived from relatively young donors (age, 14-28 years) and transplanted them into adult rats (7 weeks old). It is needed to take the limitation of the animal model into consideration for the estimation of the result of this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that allogeneic PDLSC transplantation into swine periodontal defect models did not induce immunorejection by showing no enhancement of T-cell and B-cell proliferation and immunoglobulin production and suggested the possibility of periodontal regeneration using allogeneic PDLSCs. 8,31 In this study, we used PDLSCs derived from relatively young donors (age, 14-28 years) and transplanted them into adult rats (7 weeks old). It is needed to take the limitation of the animal model into consideration for the estimation of the result of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, human autologous MSCs have been successfully used in the clinical treatment of long bone defects and osteonecrosis of the femoral head (Garg et al , ; Sim et al , ; Chapman et al , ; Connolly, ; Kawate et al , ). In addition, allogeneic MSCs derived from adipose tissue and dental tissue have the capacity to regenerate bone without the need for immunosuppressive therapy and show similar regenerative effects to those observed in autologous MSC implantation (Ding et al , ; Liu et al , ,b). Nevertheless, although a variety of literature reports have shown the efficacy and safety of using MSCs for bone regeneration, no such use has yet been approved by the US Food and Drug Administration (FDA).…”
Section: Mscs In Cell‐based Bone Regenerationmentioning
confidence: 96%
“…Additionally, there is data suggesting that MSCs suppress B cells through PDL1/PD1 pathway [102]. Another study by Liu et al demonstrates that periodontal ligament stem cells inhibit B cell activation through PDL1/PD1 [103]. These results suggest that stem cells act on the humoral immune responses through the PDL1/PD1 pathway.…”
Section: Common Snps In the Immunoregulatory Pathways Of Msc's Intmentioning
confidence: 99%